PENINGKATAN PENGETAHUAN DAN KETRAMPILAN MENGGOSOK GIGI PADA ANAK SEKOLAH DASAR DALAM RANGKA PENCEGAHAN PENYAKIT TIDAK MENULAR (PTM) MELALUI TELEPROMOSI VIDEO ANIMASI KESEHATAN GIGI - Sariyem Sariyem; Sadimin Sadimin; Wahyu Jati Diah Utami; Suwarsono Suwarsono (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2024)
The success of dental health counseling for school children cannot be separated from the educationalmethod and the importance of the role of media because the role of media makes it easier for students tounderstand learning materials. Through media, the message delivered is more interesting and easy tounderstand (1). In determining the media, it must be adjusted to the characteristics and targets of thecounseling so that the message delivered can be received effectively. Animation media is a media withmoving images in its learning (2). The purpose of the community service activity is to find out knowledgeabout dental and oral health and the ability of respondents to brush their teeth properly and correctly whichis carried out on elementary school-aged children in the RT 05 RW 16 area, Padangsari Village,Banyumanik District, Semarang City. The method used in the community service is observation ofknowledge and skills in brushing teeth before and after being given an intervention, namely counselingwith animated videos on how to brush teeth properly and correctly in elementary school-aged children. Theresults of knowledge about dental health are good criteria 16% (8 respondents), sufficient criteria 30% (15respondents), and lacking criteria 54% (27 respondents). The results of observations on the ability to brushteeth in the form of a checklist of brushing teeth skills in the target group obtained the following results: atotal of 35 respondents (70%) of the skill of brushing teeth criteria are not yet skilled, while 15 (30%)respondents are categorized as skilled in brushing teeth. After 2 weeks, a re-evaluation was carried out. Theresults of observations on knowledge about maintaining dental health increased from 16% (8 respondents)to 30 respondents (60%) good criteria, sufficient criteria from 30% (15 respondents) to 40% (20respondents) for knowledge of poor criteria there is none. The results of brushing teeth skills have increasedquite well, a total of 46 respondents have the ability to brush their teeth with the criteria of being skilled92% and only 8% (4 respondents who are not yet optimal in their ability to brush their teeth.Keywords: Telepromotion, animated video, Dental health